Guyana: from economic recovery to sustained growth (World Bank WashingtonUS, 1993)
Reviews both the current macro economic conditions of the country, as well as recent developments and issues in important sectors. The report is based on a World Bank Economic Mission which visited Guyana in October-November 1991.
Additional copy located in the Secretary-General's office.